Aortic Pulsatility Index: A New Haemodynamic Measure with Prognostic Value in Advanced Heart Failure - Tania Deis; Kasper Rossing; Finn Gustafsson (Cardiac Failure Review)
Aim: To test if the newly described haemodynamic variable, aortic pulsatility index (API), predicts long-term prognosis in advanced heart failure (HF). Methods: A single-centre study on 453 HF patients (median age: 51 years; left ventricular ejection fraction [LVEF]: 19% ± 9%) referred for right heart catheterisation. API was calculated as pulse pressure/pulmonary capillary wedge pressure. Results: Log(API) correlated significantly with central venous pressure (CVP; p<0.001) and cardiac index (p<0.001) in univariable regression analysis. CVP remained associated with log(API) in a multivariable analysis including cardiac index, heart rate, log(NT-proBNP [N-terminal proB-type natriuretic peptide]), LVEF, New York Heart Association (NYHA) class III or IV and sex (p=0.01). In univariable Cox models, log(API) was a significant predictor of freedom from the combined endpoint of death, left ventricular assist device implantation, total artificial heart implantation or heart transplantation (HR 0.33; (95% CI [0.22–0.49]); p<0.001) and all-cause mortality (HR 0.56 (95% CI [0.35–0.90]); p=0.015). After adjusting for age, sex, NYHA class III or IV and estimated glomerular filtration rate in multivariable Cox models, log(API) remained a significant predictor for the combined endpoint (HR 0.33; 95% CI [0.20–0.56]; p<0.001) and all-cause mortality (HR 0.49; 95% CI [0.26–0.96]; p=0.034). Conclusion: API was strongly associated with right-sided filling pressure and independently predicted freedom from the combined endpoint and all-cause mortality.